Managing Communicative Challenges and Interactional Dilemma: Native Speakers' Responses to Non-Native Speakers' Lack of Understanding. Issue 1 (2nd January 2020) - Terui, Sachiko; Hsieh, Elaine
ABSTRACT: Previous studies suggest non-native speakers (NNSs) use cover strategies to achieve a positive public self-image despite their lack of comprehension when interacting with native speakers (NSs). This study examines the interpersonal implications and NSs' interactional dilemma in minimizing NNSs' face threats while addressing potential miscommunication and lack of understanding in the discursive process. We arranged 14 unacquainted NS–NNS pairs (n = 28) to engage in nondirected, informal conversations (mean = 44.3 minutes; SD = 10.3). Follow-up interviews with five NSs were conducted (mean = 16.6 minutes; SD = 3.54). We used Interactional Sociolinguistics to identify four types of NSs' reactions when NNSs' cover strategies or lack of understanding become noticeable: (1) collaborating and finding commonalities; (2) interpersonal distancing through NSs' repairs; (3) othering of NNSs; and (4) engaging in patronizing talk. Our findings highlight that cover strategies can result in problematic consequences even when they were initially successful: NSs' accommodations are not always helpful in reducing possible miscommunication or in developing relationships. NS–NNS power differences are negotiated, resisted, and challenged through interactions.